The book of the past as a source of new knowledge - L. A. Kozhevnikova; V. S. Kreydenko (Библиосфера)
The role of the past book as a source of new librarianship knowledge is examined. The main purpose of this article is to characterize the views of bibliologists and library scientists on the role of books in culture development. The authors argue that the definition of the scientific truth criteria in library science, the analysis of its epistemological bases are impossible without studying evolution of the library science theory. A special role in the formation and transformation of librarianship knowledge is allotted to textbooks containing systematic information in accordance with the branch state at the time of its creation. The theoretical value of the textbook is reduced over time while the old knowledge is replaced by new one. Studying ideological dominants of the past with an old textbook, professionals maintain the cultural matrix of modern librarianship knowledge.